Genetic and phenotypic parameters of milk production in Kutchi goats - YADAV, J.S.; RAI, B; SINGH, M K; YADAV, M C; KHAN, B U (The Indian Journal of Animal Sciences, 2014)
Milk production performance of Kutchi goats was evaluated under organized farm conditions. The overall [eastsquares means for 90, 150 days, TMY, PMY and TLL were 63.46±5.12 kg, 83.52±6.96 kg, 98.44±8.04kg, 1.08±0.10 kg and 191. 56±5.44 days respectively. Sires had significantly affected the all milk performance trials. Fluctuating performance was obtained over the years and TMY, TLL and PKMY was significantly affected by year of kidding. Whereas, significantly higher 150 DMY, TMY and TLL was obtained in goats kidded during October-November months. Effect of parity was significant on milk performance traits. The h2 for 90 DMY, 150 DMY, TMY, TLL and PMY were 0.170±0.148, 0.182±0.160, 0.195±0.157, 0.133±0.136 and 0.398±0.220 respectively. Genetic and phenotypic con-elations of 90 days milk yield with other lactation traits were significant and of high magnitude.